VIKING II, a Worldwide Observational Cohort of Volunteers with Northern Isles Ancestry - Kerr, Shona; Edwards, Rachel; Buchanan, David; Dean, John; Miedzybrodzka, Zosia; Wilson, James (International Journal of Population Data Science, 2023)
Introduction The purpose of VIKING II is to create an observational cohort of volunteers with ancestry from the Northern Isles of Scotland, primarily for identifying genetic variants influencing disease. The new online protocol is separate to, but follows on from, earlier genetic epidemiological clinic-based studies in the isolated populations of Orkney and Shetland. These populations are favourable for the study of rarer genetic variants due to genetic drift, the large number of relatives, and availability of pedigree information. They are known to be genetically distinct from mainland British populations. Methods and Analysis Online methods are being used to recruit 4,000 people who have Northern Isles ancestry, living anywhere in the world. The option for participants to have actionable genetic results returned is offered. Consent will be taken electronically. Data will be collected at baseline through an online questionnaire and longitudinally through linkage to NHS data in the electronic health record. The questionnaire collects a variety of phenotypes including personal and family health. DNA will be extracted from saliva samples then genome-wide genotyped and exome sequenced. VIKING II aims to capitalise on the special features of the Northern Isles populations to create a research cohort that will facilitate the analysis of genetic variants associated with a broad range of traits and disease endpoints, including otherwise rare variants that have drifted to high frequency in these populations. Ethics and Dissemination The South East Scotland Research Ethics Committee gave the study a favourable opinion. VIKING II is sponsored by the University of Edinburgh and NHS Lothian. Summary research findings will be disseminated to participants and funding bodies, presented at conferences and reported in peer-reviewed publications. Article Summary Strengths and limitations of this study Detailed data and biological sample collection of research volunteers with unique ancestry. Consent for access to routinely collected clinical EHR data and for future re-contact, providing a longitudinal component. Optional consent for return of actionable genetic results. 4,000 participants is a relatively small number for certain types of genetic analyses, so the cohort is underpowered on its own, in some study designs. Resources to maintain the cohort, and to store data and DNA samples, are significant, with sustainability dependent on infrastructure support and funding.